2015
DOI: 10.1039/c5cp02043c
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary deformation capacity of smallest carbohelicene springs

Abstract: The extraordinary deformation and loading capacity of nine different [∞]carbohelicene springs under uniaxial tension up to their fracture were computed using the density functional theory. The simulations comprised either the experimentally synthetized springs of hexagonal rings or the hypothetical ones that contained irregularities (defects) as, for example, pentagons replacing the hexagons. The results revealed that the presence of such defects can significantly improve mechanical properties. The maximum rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“… 62 It is worth noting that such soft-spring behaviour of helicenes has also been described, or predicted, by other theoretical and experimental studies. 19 , 22 , 63 66 Fast molecular dynamics may lead to the observation of an averaged TSC value.…”
Section: Resultsmentioning
confidence: 99%
“… 62 It is worth noting that such soft-spring behaviour of helicenes has also been described, or predicted, by other theoretical and experimental studies. 19 , 22 , 63 66 Fast molecular dynamics may lead to the observation of an averaged TSC value.…”
Section: Resultsmentioning
confidence: 99%
“…It can be assumed that the difference is due to a more accurate calculation method, which was carried out within the DFT (B3LYP functional) in the TZVP basis set, taking into account the solvent and dispersion corrections. A further theoretical study of the influence of the axial deformations of [∞]helicene and its non-hexagonal modifications on mechanical stability, deformability, and fracture processes was carried out in [ 37 ] at the PBE/PAW level of theory. It was found that the presence of pentagons or heptagons instead of hexagons had a significant influence on the mechanical properties, and some helicenes could achieve very large reversible tensile strains (more than 200%).…”
Section: Theoretical Consideration Of Molecular Helicenes and Their P...mentioning
confidence: 99%
“…Among such works, we note the study of the mechanical properties of NHs by the methods of molecular dynamics [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The electronic structure of NHs of various types was studied by semi-empirical DFTB methods [ 29 , 30 , 31 ] and non-empirical DFT methods [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. It has been shown that various families of NHs are possible, including diamagnetic semiconductors, antiferromagnetic semiconductors, ferromagnets, and metals.…”
Section: Introductionmentioning
confidence: 99%